DEVELOPMENT OF KEY SKILLS OF IT SPECIALISTS THROUGH SYNERGY AND TEAMWORK - MYKHAILIUK, IRYNA; KARYCHORT, IHOR; TSAREVA, OLEKSANDRA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The aim of the research is to determine the impact of synergy on the educational process of IT students, particularly in the context of the "Group Dynamics and Communications" discipline. Special attention is given to analyzing methods for achieving synergy in teams, its impact on work productivity, and the development of key professional skills. The study employs a practical approach to organizing team work for students using the SCRUM methodology. Student teams worked on developing IT projects, following the key stages of SCRUM: project initiation, backlog formation, sprint planning and execution, and retrospectives. Team collaboration tools such as Slack and Trello were also used. To evaluate the results, participant surveys, project analysis, team interaction observations, and retrospective discussions were conducted. For the first time, the study identifies the practical impact of synergy on the educational process of IT students. It is found that synergy contributes to increased productivity, the development of soft skills (communication, leadership, active listening), and technical competencies. A set of measures aimed at achieving synergy in student teams is proposed, including conflict resolution training, effective communication workshops, and SCRUM methodology work simulations. Synergy plays an important role in forming high-performance teams, which is a key factor in the successful education of IT students. Working on projects in teams allows students to develop both individual competencies and overall team skills, leading to results that surpass the sum of individual efforts. The SCRUM methodology has shown its effectiveness in preparing students for working in real IT environments, enhancing their ability to adapt to changes, work cohesively, and innovate.